2021
DOI: 10.5688/ajpe8591
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Predictors of Success for the North American Pharmacist Licensure Examination

Abstract: Objective. Studies have examined possible predictors of success on the North American Pharmacist Licensure Examination (NAPLEX). This systematic review investigated the literature on potential predictors of success on the NAPLEX. Findings. Articles were included in the review if they included student characteristics and academic performance as independent variables and NAPLEX scores and/or pass rate as an outcome. Data were extracted from each article for students' demographics or variables, sample size, metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In our analysis of the SPLE first-time pass rate, there was a borderline significant association between the first-time pass rate and graduating from a public versus private college ( p = 0.062). A similar trend has been reported in the US as well [ 5 , 6 , 9 , 13 ]. In Saudi Arabia, public education (including universities) is free for all Saudi nationals [ 14 ], hence public universities are considered a preferred choice for the majority of high school graduates compared to private schools; this, along with the already low number of private schools, may explain the high number of applicants from public universities, compared to applicants from private schools.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our analysis of the SPLE first-time pass rate, there was a borderline significant association between the first-time pass rate and graduating from a public versus private college ( p = 0.062). A similar trend has been reported in the US as well [ 5 , 6 , 9 , 13 ]. In Saudi Arabia, public education (including universities) is free for all Saudi nationals [ 14 ], hence public universities are considered a preferred choice for the majority of high school graduates compared to private schools; this, along with the already low number of private schools, may explain the high number of applicants from public universities, compared to applicants from private schools.…”
Section: Discussionsupporting
confidence: 87%
“…Our logistic regression results showed that male applicants were less likely to pass the SPLE compared to females, although the pass rate difference was not large (95.8 vs. 97.5%, respectively). In a review of the predictors of success for NAPLEX by Park et al, they included six studies in their review that looked at applicant sex as a predictor [ 9 ]; none of the studies found a difference except for one study that reported that the mean NAPLEX score was higher by 1.65 points ( p = 0.017) in males compared to females. Due to the relatively short age of the SPLE test and the nature of the many colleges where males and females are being taught somewhat separately, this requires further studies to examine the effect of sex in greater depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies evaluated only certain predictors (ie, demographics, PCOA), and some studies combined both admission variables and pharmacy program performance variables into the same model when typically, students are assessed at admission and later evaluated for risk of failure based on program performance. 24 Combining these two sets of information into one model may reduce the impact of certain variables, because the predictor variables in the model are related and effects are canceled out. Even…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of pass rates to both C/SOPs and graduates, it is critical for C/SOPs to understand the characteristics and risk factors of pharmacy students who are most likely to benefit from supportive services during matriculation. This study and others 24 enable C/SOPs to target their scarce resources where they can make the greatest impact for student success. The purpose of this study was to evaluate two sets of comprehensive student variables for their impact on NAPLEX performance.…”
Section: Introductionmentioning
confidence: 91%